Dengue. - Whitehorn, J; Farrar, J (2010)
INTRODUCTION: Dengue is a vector-borne viral infection that endangers an estimated 2.5 billion people. Disease caused by dengue ranges from a relatively minor febrile illness to a life-threatening condition characterized by extensive capillary leak. A greater understanding of dengue has the potential to improve both the clinical management of individual cases and the control of the disease. SOURCES OF DATA: We searched the available literature using PubMed, Embase and Web of Science for relevant articles and abstracts. AREAS OF AGREEMENT: Addressing our gaps in the understanding of disease pathogenesis and improving our knowledge of dengue virus biology are necessary in order to develop tools to effectively control, diagnose and treat the disease. AREAS OF CONTROVERSY: The pathogenesis of dengue is multifactorial and depends on both host and virus factors. A more integrated understanding of disease pathogenesis is necessary. AREAS TIMELY FOR DEVELOPING RESEARCH: There are many questions related to disease pathogenesis, development of diagnostics, drug and vaccine development and individual case management that need addressing if the disease is to be successfully tackled.